Knowledge of School-Age Children About Mitigation of Mount Kelud Disaster - Umairoh, Silvia Anida; Mujito, Mujito; Rachmawati, Dewi; Bermudez, Roy Fabrigas (Health Gate, 2023)
The impact of disasters is considered more concerning for elementary school-age children, as they are unable to rescue themselves at such a young age. It is highly meaningful for elementary school-age children to have an understanding of disaster mitigation. This study aims to determine the knowledge of school children regarding the mitigation of Mount Kelud's disaster in a highly prone disaster zone. The research method used is descriptive quantitative with a population of 112 students and a sample size of 60 respondents selected through purposive sampling. Data collection was done using a questionnaire consisting of 15 questions that were validated, with a calculated value of r > r table, which is 0.602, and the reliability test result of Cronbach's alpha greater than 0.600. This research was conducted in March 2023 at SDN 02 Penataran. The research results show that the respondents' knowledge of disaster mitigation is 33.3% categorized as good, 45% as sufficient, and 21.6% as lacking. Meanwhile, knowledge in the pre-disaster phase is 31.6% good, 46.7% sufficient, and 21.6% lacking. Knowledge during a disaster is 33.3% good, 48.3% sufficient, and 18.3% lacking, while knowledge after a disaster is 26.6% good, 31.6% sufficient, and 41.6% lacking. It can be concluded that the majority of knowledge regarding disaster mitigation falls under the sufficient category, accounting for 45% with an age range of 10-13 years, and children obtain information about disaster mitigation from their families and social media. It is recommended that educational institutions incorporate disaster mitigation learning into the school curriculum to deepen students' understanding of this matter